COMPARISON OF PRESERVATIVES EFFICACY OF BENZALKONIUM CHLORIDE, THIMEROSAL AND BENZYL ALCOHOL IN EYE DROP PRODUCTS CONTAINING CHLORAMPHENICOL - KUSUMA, SRI AGUNG FITRI; ABDASSAH, MARLINE; MARYATI, FITASARY (International Journal of Applied Pharmaceutics, 2020)
Objective: The aim of this study was to compare the preservative efficacy of benzalkonium chloride, thimerosal and benzyl alcohol in eye drops formulation containing chloramphenicol as the active agents for producing the sterile and effective eye drops.Methods: The efficacy of preservatives was assayed by evaluating the physical appearance, pH stability, sterility and the antibacterial effectivity of the formulated eye drops. Each of 0.5% chloramphenicol was formulated with different preservatives of benzalkonium chloride, thimerosal and benzyl alcohol at its recommended concentration, 0.01%; 0.01% and 1%, respectively. The in vitro stability was examined periodically for the eye drops formulation stored at room temperature during the 28-day period. The effectiveness of the antibacterial effect of chloramphenicol in eye drops was assayed by using the agar diffusion method against Escherichia coli and evaluated for the diameter of inhibition zones. Result: The clarity of the eye drops formula produced clear solutions. The eye drops formula exhibited relatively stabile on pH. All the formulated eye drops were sterile during the storage time. The appropriate of the sterilization method was thought to contribute to the sterility of eye drops which did not contain preservatives. In addition, it was assumed that the pre-reaction of chloramphenicol in inhibiting the contaminants in the eye drop may occur during the storage time. This hypothesis was confirmed by the inhibitory diameter stability produced by the eye drop formulas containing preservatives compared to that of not. The decrease in inhibition diameter occurred during the storage period (28 d) of each formula was as follows: F0 (51.58%), F1 (35.76%), F2 (31.86%), and F3 (35.35%). The best stability based on the antibacterial activity of the chloramphenicol eye drops was produced by F2 which used 0.01% thimerosal as its preservative. The differences in inhibition diameter were significantly influenced by the presence and the type of preservatives. Conclusion: 0.01% thimerosal indicated the best improvement on the efficacy of 0.5% chloramphenicol eye drop.